Platelet-rich fibrin as an autologous biomaterial for bone regeneration: mechanisms, applications, optimization - Jia, Kewen; You, Jiaqian; Zhu, Yuemeng; Li, Minghui; Chen, Sheng; Ren, Sicong; Chen, Siyu; Zhang, Jingqi; Wang, Hanchi; Zhou, Yanmin (Frontiers in Bioengineering and Biotechnology, 2024)
Platelet-rich fibrin, a classical autologous-derived bioactive material, consists of a fibrin scaffold and its internal loading of growth factors, platelets, and leukocytes, with the gradual degradation of the fibrin scaffold and the slow release of physiological doses of growth factors. PRF promotes vascular regeneration, promotes the proliferation and migration of osteoblast-related cells such as mesenchymal cells, osteoblasts, and osteoclasts while having certain immunomodulatory and anti-bacterial effects. PRF has excellent osteogenic potential and has been widely used in the field of bone tissue engineering and dentistry. However, there are still some limitations of PRF, and the improvement of its biological properties is one of the most important issues to be solved. Therefore, it is often combined with bone tissue engineering scaffolds to enhance its mechanical properties and delay its degradation. In this paper, we present a systematic review of the development of platelet-rich derivatives, the structure and biological properties of PRF, osteogenic mechanisms, applications, and optimization to broaden their clinical applications and provide guidance for their clinical translation.